تأثير نظم معلومات الويب في اتخاذ القرارات- دراسة حالة المؤسسة الوطنية للدهن-وحدة سوق أهراس. - عبد الفتاح دايري; عبد الوهاب بضياف (My University, 2024)
This study aims to know the role of web Information systems in the decision-making process within organizations, as It is a topic that is in line with the requIrements of the modern era, as it can be said that web information systems help and play a decisive role In organizational decision-making processes. It supports the organization's various processes better to make appropriate decisions. Through a field study conducted at the level of the National Fat Corporation - Souk Ahras Unit, the major role played by web information systems In supporting decision-making was highlighted by studying a sample represented in time series and preparing a dashboard that contributes to Improving the quality of the decision-making process by facilitating the decision-making process between different Departments and administrative levels, by relying on the descriptive approaches on the theoretical side and the analytical on the applied side, enable efficient decision-making and influence on organizational performance. Local and external web networks are shaping the dynamics of decision making, emphasizing the need for robust systems and data quality management to obtain more detailed Insights that help make the right decisions. تهدف هذه الدراسة إلى معرفة دور نظم المعلومات الويب في عملیة اتخاذ القرار داخل المؤسسات، كونه موضوع یتماشى مع متطلبات العصر الحديث، إذ يمكن القول بأن نظم معلومات الويب تساعد و تلعب دوراً حاسماً في عمليات صنع القرار التنظيمي. وتدعم عمليات المؤسسة المختلفة بشكل أفضل لاتخاذ القرارات المناسبة. من خلال دراسة ميدانية أجريت على مستوى المؤسسة الوطنية للدهن _وحدة سوق اهراس تم إبراز الدور الكبير التي تلعبه نظم المعلومات الويب في دعم اتخاذ القرار من خلال دراسة عينة ممثلة في سلاسل زمنية وإعداد لوحة قيادة تساهم في تحسين جودة عملية اتخاذ القرار بتسهيل عملية اتخاذ القرار بين مختلف الإدارات والمستويات الإدارية، وذلك بالاعتماد على المنهجين الوصفي في الجانب النظري والتحليلي في الجانب التطبيقي تمكن من اتخاذ القرارات بكفاءة والتأثير على الأداء التنظيمي. حيث تعمل شبكات الويب المحلية والخارجية على تشكيل ديناميكيات صنع القرار، مع التركيز على الحاجة إلى أنظمة قوية وإدارة جودة البيانات للحصول على رؤى أكثر تفصيلاً تساعد على اتخاذ القرارات الصحيحة. Cette étude vise à connaître le rôle des systèmes d'information Web dans le processus décisionnel au sein des organisations, car il s'agit d'un sujet qui correspond aux exigences de l'ère moderne, car on peut dire que les systèmes d'information Web aident et jouent un rôle rôle déterminant dans les processus décisionnels organisationnels. Il soutient mieux les différents processus de l’organisation pour prendre des décisions appropriées. A travers une étude de terrain menée au niveau de la Société Nationale des Graisses - Unité Souk Ahras, le rôle majeur joué par les systèmes d'information web dans l'aide à la décision a été mis en évidence par l'étude d'un échantillon représenté en séries chronologiques et l'élaboration d'un tableau de bord qui contribue à améliorer la qualité du processus décisionnel en facilitant le processus décisionnel entre les différents départements et niveaux administratifs, en s'appuyant sur les approches descriptives du côté théorique et analytique du côté appliqué, permettent une prise de décision efficace et une influence sur la performance organisationnelle. Les réseaux Web locaux et externes façonnent la dynamique de la prise de décision, soulignant
Keywords: Keywords: web informat